Apex radicis dentis excision operation guided by template made by CAD/CAM - He, Zong-Lai (Int J Clin Exp Med, 2015)
Objective: The aim of the study is to explore the clinical efficacy of apex radicis dentis excision guided by a template made by Computer Aided Design/Computer Aided Manufacture (CAD/CAM). Methods: Base on the CBCT image of oral cavity, a three-dimensional model of patient’s oral cavity was built. Then the access way and excisional area were defined based on the model. Finally, the operative guide template was designed and made to help define the direction, depth, and area of the surgery. Results: One year after the operation with guide template, the two cases of apex radicis dentis with difficulty in cure were proven to have normal masticatory function and their pathological changes of apex radicis dentis disappeared as well. Conclusion: Utilization of CAD/CAM technology could well design the operative guide template for the resection of apex radicis dentis. Usingthis guide template could make the excision of apex radicis dentis more quickly and safer.